2022
DOI: 10.3389/fphar.2022.757729
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Epileptic Effect of Crocin on Experimental Temporal Lobe Epilepsy in Mice

Abstract: Temporal lobe epilepsy (TLE) is a common kind of refractory epilepsy. More than 30% TLE patients were multi-drug resistant. Some patients may even develop into status epilepticus (SE) because of failing to control seizures. Thus, one of the avid goals for anti-epileptic drug development is to discover novel potential compounds to treat TLE or even SE. Crocin, an effective component of Crocus sativus L., has been applied in several epileptogenic models to test its anti-epileptic effect. However, it is still con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The brain-derived neurotrophic factor (BDNF)–tropomyosin receptor kinase B (TrkB) pathway is closely associated with epilepsy. Crocin can increase the BDNF level in the cortex of temporal lobe epilepsy and reduce the content of tumor necrosis factor α (TNF-α) in the hippocampus, thereby playing an antiepileptic role [ 41 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…The brain-derived neurotrophic factor (BDNF)–tropomyosin receptor kinase B (TrkB) pathway is closely associated with epilepsy. Crocin can increase the BDNF level in the cortex of temporal lobe epilepsy and reduce the content of tumor necrosis factor α (TNF-α) in the hippocampus, thereby playing an antiepileptic role [ 41 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…Modern pharmacological studies have shown that crocin has various pharmacological activities, including anti-oxidant ( Amin et al, 2014 ; Finley & Gao, 2017 ), anti-aging ( Mohammadi et al, 2018 ), anti-inflammatory ( Li et al, 2018 ; Liu et al, 2018 ; Yarijani et al, 2017 ), anti-liver fibrosis ( Algandaby, 2018 ), anti-hyperlipidemia ( Sheng et al, 2006 ), anti-epilepsy ( Zhong et al, 2022 ), anti-anxiety and depression ( Salek et al, 2021 ; Xiao et al, 2020 ), anti-cancer ( Hoshyar & Mollaei, 2017 ; Jiang et al, 2018 ; Rahaiee et al, 2017 ), anti-stone ( Ghaeni et al, 2014 ) and neuro-protective ( Mozaffari et al, 2019 ) effects. Therefore, crocin has become a hot research topic in recent years with its significant effectiveness, low toxicity and high safety.…”
Section: Introductionmentioning
confidence: 99%